2019
DOI: 10.1017/jfm.2019.45
|View full text |Cite
|
Sign up to set email alerts
|

The cell-free layer in simulated microvascular networks

Abstract: In the microcirculation, a plasma layer forms near the vessel walls that is free of red blood cells (RBCs). This region, often termed as the cell-free layer (CFL), plays important haemorheological and biophysical roles, and has been the subject of extensive research. Many previous studies have considered the CFL development in single, isolated vessels that are straight tubes or channels, as well as in isolated bifurcations and mergers. In the body, blood vessels are typically winding and sequentially bifurcate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 59 publications
5
24
0
Order By: Relevance
“…Our RBC simulations confirmed previous reports of transient alterations in the CFL downstream of network bifurcations (e.g. asymmetries in the cross-sectional haematocrit profile following a bifurcation [46,47] and the temporal dynamics governing its axisymmetry recovery [37]). Further, for the λ values measured in our tumours and the capillary number considered in our simulations, the CFL did not become symmetric between consecutive branching points.…”
Section: Vascular Normalisation Therapies Increase λ Ratio In Tumourssupporting
confidence: 88%
“…Our RBC simulations confirmed previous reports of transient alterations in the CFL downstream of network bifurcations (e.g. asymmetries in the cross-sectional haematocrit profile following a bifurcation [46,47] and the temporal dynamics governing its axisymmetry recovery [37]). Further, for the λ values measured in our tumours and the capillary number considered in our simulations, the CFL did not become symmetric between consecutive branching points.…”
Section: Vascular Normalisation Therapies Increase λ Ratio In Tumourssupporting
confidence: 88%
“…There exists no study that systematically addresses such changes in equilibria as inertia is gradually increased. Furthermore, as predicted by Balogh & Bagchi (2019) and discussed previously, particle migration seems to be affected not only by the vessel curvature, but also by the change in curvature. There exists no study that considers the effect of curvature change on migration.…”
Section: Migration Of Particles In Curved Vessels With Inertiasupporting
confidence: 71%
“…A somewhat related study is the numerical simulations performed by Balogh & Bagchi (2019) on the flow of red blood cell suspensions in arbitrarily curved vessels in large microvascular networks resembling physiological geometry. They observed that cells move closer to the inner wall (that is, the side with higher curvature) of a vessel.…”
Section: Introductionmentioning
confidence: 99%
“…These experimental limitations can be potentially overcome by increasingly realistic computational simulations, which can query multiple aspects that are otherwise inconvenient or inaccessible to experiments, such as microscopic cell dynamics in a dense suspension, emergent cell orderings on the crosssectional plane and spatio-temporal RBC flow properties (e.g. evolving CFLs [22,23]).…”
Section: Introductionmentioning
confidence: 99%